Species diversity of the genus Osmundea (Ceramiales, Rhodophyta) in the Macaronesian region. Issue 4 (20th July 2016) - Machín‐Sánchez, María; Rousseau, Florence; Le Gall, Line; Cassano, Valéria; Neto, Ana I.; Sentíes, Abel; T. Fujii, Mutue; Gil‐Rodríguez, María Candelaria
Abstract : Species diversity within the genus Osmundea in the Macaronesian region was explored by conducting a comprehensive sampling in the Azores, the Canary, and the Madeira archipelagos. Toward identification, all specimens were first observed alive to verify the absence of corps en cerise, a diagnostic character for the genus and morphometric data were measured (thallus length and width, first‐order branches length and width, branchlets length and width, cortical cell length and width in surface view, cortical cell length and width in transverse section). Specimens were sequenced for COI‐5P (39 specimens) and three species delimitation methods (Generalized Mixed Yule Coalescent, Automatic Barcode Gap Discovery method, and Poisson Tree Processes) were used to assess the threshold between infra‐ and interspecific relationships. Subsequently, one or several sequences of plastid‐encoded large subunit of RuBisCO (21 specimens) per delimited species were generated to assess the phylogenetic relationships among Macaronesian Osmundea . Moreover, for each delineated species, vegetative and reproductive anatomy was thoroughly documented and, when possible, specimens were either assigned to existing taxa or described as novel species. This integrative approach has provided data for (i) the presence of O. oederi, O. pinnatifida, and O. truncata in Macaronesia; (ii) the proposal of two novel species, O. prudhommevanreinei sp. nov. and O. silvae sp. nov.; and (iii) evidence of an additional species referred as " Osmundea sp.1, " which is a sister taxon of O. hybrida .